Расчёт скорости и времени сушки огнеупорных материалов - Никифоров, А. С.; Приходько , Е. В.; Кинжибекова, А. К.; Жумагулов, М. Г.; Карманов, А. Е.; Нуркина, Ш. М. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
Расчёт скорости и времени сушки огнеупорных материалов